ANALYSIS OF SERVICE BUSINESS GROWTH AND MARKETING STRATEGIES USED IN THE DIGITAL TECHNOLOGY ERA DURING THE COVID-19 PANDEMIC: (Case Study on PT. Sucofindo Medan) - Nasution, Meirizka Miranda; Dirbawanto, Nana Dyki; Siregar, Onan Marakali (Transpublika Publisher, 2023)
In the current era of the COVID-19 pandemic, people are expected to be able to engage directly in the digital world. As done by PT. Sucofindo Medan. Continuous technological innovation is the company's obligation to be able to compete with competitors. Therefore, PT. Sucofindo Medan must update the marketing strategy used. The aim of this research is to analyze the growth of the service business and marketing strategies used in the digital era during the COVID-19 pandemic at PT. Sucofindo. The theory used is to look at the company's Value Preposition which is connected to the marketing mix indicator. Based on the research results, it is known that the application of Value Preposition becomes a company evaluation based on the Customer Profile indicator, namely Customer Jobs, pains, and gains, which explain the desires and obstacles felt by consumers. The company provides solutions for Product and Services indicators, Gain Creators and Pain Relievers. The combination of Value Preposition Marketing Mix on company promotion indicators can be improved by developing many applications that can help potential customers, one of which is KSO-SCISI, which is able to monitor orders, receive payments, and accommodate customer feedback so that service is more optimal.